Polyanion-doped sulfate carbon-coated sodium ion composite positive electrode material and preparation thereof
Through the preparation method of polyanion-doped sulfate carbon-coated manganese titanium vanadium sodium composite material NMTVPS@C, the high energy consumption and low cycle stability of the existing sodium ion battery positive electrode materials are solved, and excellent performance and cost-effectiveness are achieved Controlled cathode material, suitable for large-scale production.
Patent Information
- Application Number
- CN202411475653.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-22
- Publication Date
- 2025-02-11
AI Technical Summary
The existing sodium ion battery positive electrode materials have problems such as high synthesis temperature, high energy consumption, poor cycle stability, low working potential, poor rate performance, high production costs, poor economic benefits and environmental benefits.
The preparation method of polyanionic doped sulfate carbon coated manganese titanium vanadium sodium composite material NMTVPS@C is adopted. The performance is prepared by heating, spray drying and sintering of a mixed solution of titanium citrate complex and other metal salts. Excellent positive electrode material.
This method effectively avoids the problem of mutual occupation of sodium ions and manganese ions, improves the conductivity, energy and power characteristics of the cathode material, reduces production costs, and is suitable for large-scale production.
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of batteries, and in particular relates to a polyanion-doped sulfate-carbon-coated sodium ion composite positive electrode material NMTVPS@C and a preparation method thereof. Background Art
[0002] The working principle of sodium-ion batteries is similar to that of lithium-ion batteries. Energy is stored and released through the redox reaction of sodium ions at the positive and negative electrodes. The core components of sodium-ion batteries include positive electrodes, negative electrodes and electrolytes. During charging, sodium ions are released from the positive electrode active material and embedded in the negative electrode active material; during discharge, sodium ions are released from the negative electrode active material and embedded in the positive electrode active material. At present, the positive electrode materials used in sodium-ion batteries mainly include layered metal oxides, Prussian blue or Prussian white compounds, and polyanion positive electrode materials. They generally have many problems such as high synthesis temperature, high energy consumption, poor cycle stability, low working potential, unsatisfactory rate performance, high production cost, poor economic and environmental benefits, etc.
[0003] The sodium manganese titanium vanadium phosphate cathode composite material NMTVPS@C has significant advantages such as high operating voltage. However, due to the low intrinsic conductivity of its pure phase material, it seriously affects the sodium storage electrochemical performance of this type of cathode material, showing low sodium storage specific capacity, poor long-cycle stability and high-rate performance.
[0004] Based on the above-mentioned technical problems, the present invention comes from this. Summary of the invention
[0005] In view of the above-mentioned deficiencies in the prior art, the present invention provides a polyanion-doped sulfate carbon-coated sodium ion composite positive electrode material NMTVPS@C and a preparation method thereof. The preparation method is easy to operate, effectively avoids the problem of sodium ion and manganese ion occupying each other's positions, and the obtained product has excellent performance, controllable cost, and is suitable for large-scale production.
[0006] The technical solution of the present invention is:
[0007] The present invention relates to a method for preparing a polyanion-doped sulfate-carbon-coated sodium ion composite positive electrode material, comprising the following steps:
[0008] (1) preparing a mixed solution of titanium citrate and ammonium sulfate;
[0009] (2) mixing high-purity water, citric acid, vanadium salt, manganese salt, phosphate, sodium salt, and the mixed solution obtained in step (1) to prepare a sodium ion positive electrode material precursor mixed solution;
[0010] (3) heating the mixed solution obtained in step (2) to obtain a precursor sol;
[0011] (4) then spray drying the precursor sol to obtain a precursor;
[0012] (5) The precursor is sintered, crushed and dried under a protective gas atmosphere to obtain a polyanion-doped sulfate-carbon-coated manganese titanium vanadium sodium phosphate composite sodium ion positive electrode material NMTVPS@C.
[0013] Preferably, the preparation process of the mixed solution of titanium citrate and ammonium sulfate is: react high-purity TiO2 with concentrated sulfuric acid, and then add high-purity water to obtain a high-purity titanyl sulfate solution; then add ammonia water to adjust the pH to 3-4 to obtain a mixture of white precipitate of titanic acid and ammonium sulfate; continue to add appropriate amounts of citric acid and high-purity water, the precipitate of titanic acid dissolves, and a mixed solution of titanium citrate and ammonium sulfate is formed.
[0014] Preferably, in the preparation of a mixed solution of titanium citrate and ammonium sulfate, the molar ratio of TiO2 in high-purity TiO2 to sulfate and citric acid in concentrated sulfuric acid is 0.6:0.6:1, and concentrated sulfuric acid is used as a dopant.
[0015] Preferably, the reaction conditions of high-purity TiO2 and high-purity concentrated sulfuric acid are: 120°C for 2 hours. The molecular formula of titanium oxysulfate hydrate is: TiOSO4.3H2O, the purity of high-purity TiO2 is 99.5%, and the mass concentration of concentrated sulfuric acid is greater than or equal to 98%.
[0016] Preferably, the mass concentration of the ammonia water is 25-28%.
[0017] Preferably, the manganese salt is manganese acetate tetrahydrate or manganese carbonate, the vanadium salt is ammonium metavanadate, the phosphate is sodium dihydrogen phosphate, and the sodium salt is sodium acetate or sodium carbonate;
[0018] In terms of molar ratio, V in vanadium salt: Mn in manganese salt: sodium dihydrogen phosphate: Na in sodium salt: TiO2 = 0.4: 1: 2.6: 0.8: 0.6, the total molar amount of high-purity water used to prepare the mixed solution of sodium ion positive electrode material precursor to the molar amount of manganese salt is (550-620): 1, and the total molar amount of citric acid used to prepare the mixed solution of sodium ion positive electrode material precursor to the mass ratio of manganese salt is (2-3): 1. The total molar amount of high-purity water includes not only the high-purity water used to prepare the mixed solution of titanium citrate and ammonium sulfate, but also the high-purity water used in step (2); the total molar amount of citric acid includes not only the citric acid used to prepare the mixed solution of titanium citrate and ammonium sulfate, but also the citric acid used in step (2).
[0019] Preferably, the manganese salt is manganese acetate tetrahydrate or manganese carbonate, the vanadium salt is ammonium metavanadate, the phosphate is ammonium dihydrogen phosphate, and the sodium salt is sodium acetate or sodium carbonate;
[0020] In terms of molar ratio, V in vanadium salt: Mn in manganese salt: diammonium hydrogen phosphate: Na in sodium salt: TiO2 = 0.4:1:2.6:3.4:0.6, the ratio of the total molar amount of high-purity water used to prepare the mixed solution of sodium ion positive electrode material precursor to the molar amount of manganese salt is (550-620):1, and the ratio of the total molar amount of citric acid used to prepare the mixed solution of sodium ion positive electrode material precursor to the mass of manganese salt is (2-3):1.
[0021] Preferably, in step (3), the mixed solution obtained in step (2) is heated to 80° C. and kept warm for 60-120 minutes.
[0022] Preferably, in step (4), the temperature conditions for spray drying are: controlling the inlet air temperature at 300°C to 350°C and the outlet temperature at 105-108°C.
[0023] Preferably, in step (5), the sintering conditions are: in a protective gas atmosphere, heating to 700° C. within 240 minutes and keeping the temperature for 8-18 hours.
[0024] The present invention also relates to a polyanion-doped sulfate-carbon-coated sodium ion composite positive electrode material, which is prepared by the above-mentioned preparation method and has a coated carbon content of 8-10.5%. The chemical formula of the composite positive electrode material is: Na 3.4 MnTi 0.6 V 0.4 (PO4) 2.6 (SO4) 0.6 @C.
[0025] The beneficial effects of the present invention are:
[0026] (1) The present invention first prepares a citric acid titanium complex solution slurry, and then uses sol spray drying to synthesize a polyanion-doped sulfate carbon-coated sodium manganese titanium vanadium phosphate composite positive electrode material precursor, and sintering to obtain a carbon-coated positive electrode composite material, which helps to simplify the process steps of material synthesis and reduce energy consumption. Sol spray drying can effectively control the particle size of the synthetic material and enhance the conductivity of the polyanion-doped sulfate carbon-coated sodium manganese titanium vanadium phosphate composite material NMTVPS@C;
[0027] (2) The sodium ions and manganese ions in the particles of the positive electrode material prepared by the present invention avoid occupying each other, and the sodium ions are more easily released. The carbon film is coated to form a nanofiber channel with high thermal and electrical conductivity, which greatly improves the energy and power characteristics of the positive electrode material. DETAILED DESCRIPTION
[0028] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention is further described in detail below in conjunction with specific embodiments. It should be understood that these descriptions are exemplary only and are not intended to limit the scope of the present invention. In addition, in the following description, the description of known structures and technologies is omitted to avoid unnecessary confusion of the concept of the present invention.
[0029] Embodiment 1:
[0030] Na 3.4 MnTi 0.6 V 0.4 (PO4) 2.6 (SO4) 0.6 Preparation of @C:
[0031] S1. Weigh 2.408 g of 99.5% high-purity TiO2, add it to 3 g of 98% (mass concentration) concentrated sulfuric acid, stir evenly, and react in an acid-resistant reactor at 120°C for 2 h. After the reaction, add 50 g of high-purity water to obtain 55.408 g of high-purity titanyl sulfate solution with a solid content of 8.66%.
[0032] S2. Add 8.16 g of 25% (mass concentration) ammonia water, adjust the pH to 3-4, and obtain a white precipitate of metatitanic acid and a by-product of ammonium sulfate.
[0033] S3. Weigh 9.704 g of 99% anhydrous citric acid and dissolve it in 100 g of high-purity water. Add the titanic acid precipitate and by-product solution obtained in S2 to the above citric acid aqueous solution and stir evenly to obtain a citrate titanium complex solution.
[0034] S4. 173.26 g of the titanium citrate complex aqueous solution is used in the production of the precursor, the molar ratio of titanium content to sulfate content is 1:1, the titanium content is 0.828%, and the sulfate content is 1.66%.
[0035] S5. Weigh 250g of high-purity water, add 9.704g of 99% anhydrous citric acid, stir evenly and dissolve.
[0036] S6. Weigh 2.3514 g of 99.5% ammonium metavanadate, add it to the citric acid aqueous solution obtained in step S5, and stir for 10 minutes.
[0037] S7. Weigh 12.3783 g of 99.0% manganese acetate tetrahydrate, add it to the aqueous solution of ammonium metavanadate obtained in step S6, and stir for 10 minutes.
[0038] S8. Weigh 15.7522 g of 99.0% sodium dihydrogen phosphate, add 100 g of high-purity water, dissolve it, and add it to the lemon-manganese-vanadium mixed solution obtained in step S7, and stir for 10 minutes.
[0039] S9. Weigh 3.3144 g of 99% anhydrous sodium acetate, add it to the mixed solution obtained in step S8, and stir for 10 minutes.
[0040] S10. Finally, 173.26 g of the titanium citrate complex solution was added to obtain a mixed solution.
[0041] S11, heating the mixed solution obtained in step S10 to 80°C and keeping the temperature for 120 minutes to obtain Na 3.4 MnTi 0.6 V 0.4 (PO4) 2.6 (SO4) 0.6 @C precursor sol 450g.
[0042] S12, controlling the air inlet temperature at 300-350°C and the air outlet temperature at 105-108°C, spray drying the precursor sol, and obtaining 42.5 g of the precursor.
[0043] S13. Under inert gas atmosphere (Ar), the above-mentioned cathode material precursor is heated to 700°C for 240 minutes and kept warm for 12 hours, then cooled and crushed with a small airflow mill to obtain a polyanion-doped sulfate-carbon-coated manganese titanium vanadium sodium phosphate composite material NMTVPS@C. The measured cumulative particle size distribution numbers are: D10=1.2μm, D50=2.8μm, D90=5.6μm, Dmax=15.5μm, and the carbon content of the material is 8.88%.
[0044] Embodiment 2:
[0045] Na 3.4 MnTi 0.6 V 0.4 (PO4) 2.6 (SO4) 0.6 Preparation of @C:
[0046] S1. Weigh 2.408 g of 99.5% high-purity TiO2, add it to 3 g of 98% (mass concentration) concentrated sulfuric acid, stir evenly, and react in an acid-resistant reactor at 120°C for 2 h. After the reaction, add 50 g of high-purity water to obtain 55.408 g of high-purity titanyl sulfate solution with a solid content of 8.66%.
[0047] S2. Add 8.16 g of 25% (mass concentration) ammonia water, adjust the pH to 3-4, and obtain a white precipitate of metatitanic acid and a by-product of ammonium sulfate.
[0048] S3. Weigh 9.704 g of 99% anhydrous citric acid and dissolve it in 100 g of high-purity water. Add the titanic acid precipitate and by-product solution obtained in S2 to the above citric acid aqueous solution and stir evenly to obtain a citrate titanium complex solution.
[0049] S4. 173.26 g of the titanium citrate complex aqueous solution is used in the production of the precursor, the molar ratio of titanium content to sulfate content is 1:1, the titanium content is 0.828%, and the sulfate content is 1.66%.
[0050] S5. Weigh 250 g of high-purity water, add 9.704 g of 99% anhydrous citric acid, stir evenly and dissolve.
[0051] S6. Weigh 5.8056 g of manganese carbonate with a Mn content of 44-48%, add it to the citric acid aqueous solution obtained in step S5, and stir for 10 minutes.
[0052] S7. Weigh 2.3514 g of 99% ammonium metavanadate, add it to the citric acid-manganese mixed solution obtained in step S6, and stir for 10 minutes.
[0053] S8. Weigh 15.7522 g of 99.0% sodium dihydrogen phosphate, add 100 g of high-purity water, dissolve it, and add it to the lemon-manganese-vanadium mixed solution obtained in step S7, and stir for 10 minutes.
[0054] S9. Weigh 2.124 g of 99.8% anhydrous sodium carbonate, add it to the mixed solution obtained in step S8, and stir for 10 minutes.
[0055] S10. Finally, 173.26 g of the titanium citrate complex solution was added to obtain a mixed solution.
[0056] S11, heat the mixed solution to 80°C and keep it warm for 120 minutes to obtain Na 3.4 MnTi 0.6 V 0.4 (PO4) 2.6 (SO4) 0.6 @C precursor sol 440g.
[0057] S12, controlling the air inlet temperature at 300-350°C and the air outlet temperature at 105-108°C, spray drying the precursor sol, and obtaining 41.3 g of the precursor.
[0058] S13. Under inert gas atmosphere (Ar), the above-mentioned cathode material precursor is heated to 700°C for 240 minutes and kept warm for 12 hours, then cooled and crushed with a small airflow mill to obtain a polyanion-doped sulfate-carbon-coated manganese titanium vanadium sodium phosphate composite material NMTVPS@C. The measured cumulative particle size distribution numbers are: D10=1.8μm, D50=3.8μm, D90=6.9μm, Dmax=16.5μm, and the carbon content of the material is 8.85%.
[0059] Embodiment 3:
[0060] Na 3.4 MnTi0.6 V 0.4 (PO4) 2.6 (SO4) 0.6 Preparation of @C:
[0061] S1. Weigh 2.408 g of 99.5% high-purity TiO2, add it to 3 g of 98% (mass concentration) concentrated sulfuric acid, stir evenly, and react in an acid-resistant reactor at 120°C for 2 h. After the reaction, add 50 g of high-purity water to obtain 55.408 g of high-purity titanyl sulfate solution with a solid content of 8.66%.
[0062] S2. Add 8.16 g of 25% (mass concentration) ammonia water, adjust the pH to 3-4, and obtain a white precipitate of metatitanic acid and a by-product of ammonium sulfate.
[0063] S3. Weigh 9.704 g of 99% anhydrous citric acid and dissolve it in 100 g of high-purity water. Add the titanic acid precipitate and by-product solution obtained in S2 to the above citric acid aqueous solution and stir evenly to obtain a citrate titanium complex solution.
[0064] S4. 173.26 g of the titanium citrate complex aqueous solution is used in the production of the precursor, the molar ratio of titanium content to sulfate content is 1:1, the titanium content is 0.828%, and the sulfate content is 1.66%.
[0065] S5. Weigh 250g of high-purity water, add 14.5553g of 99% anhydrous citric acid, stir evenly and dissolve.
[0066] S6. Weigh 12.3783 g of 99.0% manganese acetate tetrahydrate, add it to the citric acid aqueous solution obtained in step S5, and stir for 10 minutes.
[0067] S7. Weigh 2.3514 g of 99.5% ammonium metavanadate, add it to the citric acid-manganese mixed solution obtained in step S6, and stir for 10 minutes.
[0068] S8. Weigh 15.6414 g of 99.0% ammonium dihydrogen phosphate, add 100 g of high-purity water, dissolve it, and add it to the lemon-manganese-vanadium mixed solution obtained in step S7, and stir for 10 minutes.
[0069] S9. Weigh 14.0862 g of 99% anhydrous sodium acetate, add 50 g of high-purity water to dissolve it, add it to the mixed solution obtained in step S8, and stir for 10 minutes.
[0070] S10. Finally, 173.26 g of titanium citrate complex sol was added to obtain 632.2726 g of a mixed solution.
[0071] S11, heating the mixed solution obtained in step S10 to 80°C and keeping the temperature for 120 minutes to obtain Na 3.4 MnTi0.6 V 0.4 (PO4) 2.6 (SO4) 0.6 @C precursor sol 485g.
[0072] S12, controlling the air inlet temperature at 300-350°C and the air outlet temperature at 105-108°C, spray drying the precursor sol, and obtaining 44.5 g of the precursor.
[0073] S13. Under inert gas atmosphere (Ar), the above-mentioned cathode material precursor is heated to 700°C for 240 minutes and kept warm for 12 hours, then cooled and crushed with a small airflow mill to obtain a polyanion-doped sulfate carbon-coated manganese titanium vanadium sodium phosphate composite material NMTVPS@C. The measured cumulative particle size distribution numbers are: D10=1.3μm, D50=3μm, D90=6.8μm, Dmax=17.5μm, and the carbon content of the material is 9.5%.
[0074] Example 4
[0075] Na 3.4 MnTi 0.6 V 0.4 (PO4) 2.6 (SO4) 0.6 Preparation of @C:
[0076] S1. Weigh 2.408 g of 99.5% high-purity TiO2, add it to 3 g of 98% (mass concentration) concentrated sulfuric acid, stir evenly, and react in an acid-resistant reactor at 120°C for 2 h. After the reaction, add 50 g of high-purity water to obtain 55.408 g of high-purity titanyl sulfate solution with a solid content of 8.66%.
[0077] S2. Add 8.16 g of 25% (mass concentration) ammonia water, adjust the pH to 3-4, and obtain a white precipitate of metatitanic acid and a by-product of ammonium sulfate.
[0078] S3. Weigh 9.704 g of 99% anhydrous citric acid and dissolve it in 100 g of high-purity water. Add the titanic acid precipitate and by-product solution obtained in S2 to the above citric acid aqueous solution and stir evenly to obtain a citrate titanium complex solution.
[0079] S4. 173.26 g of the titanium citrate complex aqueous solution is used in the precursor production, the molar ratio of titanium content to sulfate content is 1:1, the titanium content is 0.828%, and the sulfate content is 1.66%.
[0080] S5. Weigh 250g of high-purity water, add 14.5553g of 99% citric acid, stir evenly and dissolve.
[0081] S6. Weigh 5.8056 g of manganese carbonate with a Mn content of 44-48%, add it to the citric acid aqueous solution obtained in step S5, and stir for 10 minutes.
[0082] S7. Weigh 2.3514 g of 99.5% ammonium metavanadate, add it to the citric acid-manganese mixed solution obtained in step S6, and stir for 10 minutes.
[0083] S8. Weigh 15.6414 g of 99.0% ammonium dihydrogen phosphate, add 100 g of high-purity water, dissolve it, and add it to the lemon-manganese-vanadium mixed solution obtained in step S7, and stir for 10 minutes.
[0084] S9. Weigh 9.0272 g of 99% anhydrous sodium carbonate, add 50 g of pure water to dissolve it, then add it titratingly into the mixed solution obtained in step S8, and stir for 10 minutes.
[0085] S10. Finally, 173.26 g of titanium citrate complex sol was added to obtain a mixed solution.
[0086] S11, heat the mixed solution to 80°C and keep it warm for 120 minutes to obtain Na 3.4 MnTi 0.6 V 0.4 (PO4) 2.6 (SO4) 0.6 @C precursor sol 474.02g.
[0087] S12, controlling the air inlet temperature at 300-350°C and the air outlet temperature at 105-108°C, spray drying the precursor sol, and obtaining 42.5 g of the precursor.
[0088] S13. Under inert gas atmosphere (Ar), the above-mentioned cathode material precursor is heated to 700°C for 240 minutes and kept warm for 16 hours, then cooled and crushed with a small airflow mill to obtain a polyanion-doped sulfate-carbon-coated manganese titanium vanadium sodium phosphate composite material NMTVPS@C. The measured cumulative particle size distribution numbers are: D10=1.4μm, D50=3.8μm, D90=6.6μm, Dmax=17.5μm, and the carbon content of the material is 9.4%.
[0089] Example 5
[0090] Na 3.4 MnTi 0.6 V 0.4 (PO4) 2.6 (SO4) 0.6 Preparation of @C:
[0091] S1. Weigh 2.408 g of 99.5% high-purity TiO2, add it to 3 g of 98% (mass concentration) concentrated sulfuric acid, stir evenly, and react in an acid-resistant reactor at 120°C for 2 h. After the reaction, add 50 g of high-purity water to obtain 55.408 g of high-purity titanyl sulfate solution with a solid content of 8.66%.
[0092] S2. Add 8.16 g of 25% (mass concentration) ammonia water, adjust the pH to 3-4, and obtain a white precipitate of metatitanic acid and a by-product of ammonium sulfate.
[0093] S3. Weigh 9.704 g of 99% anhydrous citric acid and dissolve it in 100 g of high-purity water. Add the titanic acid precipitate and by-product solution obtained in S2 to the above citric acid aqueous solution and stir evenly to obtain a citrate titanium complex solution.
[0094] S4. 173.26 g of the titanium citrate complex aqueous solution is used in the precursor production, the molar ratio of titanium content to sulfate content is 1:1, the titanium content is 0.828%, and the sulfate content is 1.66%.
[0095] S5. Weigh 250 g of high-purity water, add 19.407 g of 99% anhydrous citric acid, stir evenly and dissolve.
[0096] S6. Weigh 12.3783 g of 99.0% manganese acetate tetrahydrate, add it to the citric acid aqueous solution, and stir for 10 minutes.
[0097] S7. Weigh 2.3514 g of 99.5% ammonium metavanadate, add it to the citric acid-manganese mixed solution, and stir for 10 minutes.
[0098] S8. Weigh 15.7522 g of 99.0% sodium dihydrogen phosphate, add 100 g of high-purity water, dissolve it, add it to the lemon-manganese-vanadium mixed solution, and stir for 10 minutes.
[0099] S9. Weigh 3.3144 g of 99% anhydrous sodium acetate, add it to the mixed solution, and stir for 10 minutes.
[0100] S10. Finally, 173.26 g of the titanium citrate complex solution was added to obtain 576.4633 g of a mixed solution.
[0101] S11, heat the mixed solution to 80°C and keep it warm for 120 minutes to obtain Na 3.4 MnTi 0.6 V 0.4 (PO4) 2.6 (SO4) 0.6 @C precursor sol 480g.
[0102] S12, controlling the air inlet temperature to 300-350°C and the air outlet temperature to 105-108°C, spray drying the precursor sol to obtain 48.5 g of the precursor.
[0103] S13. Under inert gas atmosphere (Ar), the cathode material precursor is heated to 700°C for 240-360 minutes and kept at this temperature for 16 hours, then cooled and crushed with a small airflow mill to obtain a polyanion-doped sulfate-carbon-coated manganese titanium vanadium sodium phosphate composite material NMTVPS@C. The cumulative particle size distribution numbers are measured as follows: D10=1.8μm, D50=3.8μm, D90=6.6μm, Dmax=17.5μm, and the carbon content of the material is 10.2%.
[0104] Example 6
[0105] Na 3.4 MnTi 0.6 V 0.4 (PO4) 2.6 (SO4) 0.6 Preparation of @C
[0106] S1. Weigh 2.408 g of 99.5% high-purity TiO2, add it to 3 g of 98% (mass concentration) concentrated sulfuric acid, stir evenly, and react in an acid-resistant reactor at 120°C for 2 h. After the reaction, add 50 g of high-purity water to obtain 55.408 g of high-purity titanyl sulfate solution with a solid content of 8.66%.
[0107] S2. Add 8.16 g of 25% (mass concentration) ammonia water, adjust the pH to 3-4, and obtain a white precipitate of metatitanic acid and a by-product of ammonium sulfate.
[0108] S3. Weigh 9.704 g of 99% anhydrous citric acid and dissolve it in 100 g of high-purity water. Add the titanic acid precipitate and by-product solution obtained in S2 to the above citric acid aqueous solution and stir evenly to obtain a citrate titanium complex solution.
[0109] S4. 173.26 g of the titanium citrate complex aqueous solution is used in the precursor production, the molar ratio of titanium content to sulfate content is 1:1, the titanium content is 0.828%, and the sulfate content is 1.66%.
[0110] S5. Weigh 250 g of high-purity water, add 19.407 g of 99% anhydrous citric acid, stir evenly and dissolve.
[0111] S6. Weigh 5.8056 g of manganese carbonate with a Mn content of 44-48%, add it to the citric acid aqueous solution obtained in step S5, and stir for 10 minutes.
[0112] S7. Weigh 2.3514 g of 99.5% ammonium metavanadate, add it to the citric acid-manganese mixed solution obtained in step S6, and stir for 10 minutes.
[0113] S8. Weigh 15.7522 g of 99.0% sodium dihydrogen phosphate, add 100 g of high-purity water, dissolve it, and add it to the lemon-manganese-vanadium mixed solution obtained in step S7, and stir for 10 minutes.
[0114] S9. Weigh 3.3144 g of 99% anhydrous sodium acetate, add it to the mixed solution obtained in step S8, and stir for 10 minutes.
[0115] S10. Finally, 173.26 g of the titanium citrate complex solution was added to obtain a mixed solution.
[0116] S11, heat the mixed solution to 80°C and keep it warm for 120 minutes to obtain Na 3.4 MnTi 0.6 V 0.4 (PO4) 2.6 (SO4) 0.6 @C precursor sol 450g.
[0117] S12, controlling the air inlet temperature to 300-350°C and the air outlet temperature to 105-108°C, spray drying the precursor sol to obtain 46 g of the precursor.
[0118] S13. Under inert gas atmosphere (Ar), the above-mentioned positive electrode material precursor is heated to 700°C for 240 minutes and kept warm for 16 hours, then cooled and crushed with a small airflow mill to obtain a polyanion-doped sulfate-carbon-coated manganese titanium vanadium sodium phosphate composite material NMTVPS@C. The measured cumulative particle size distribution numbers are: D10=1.5μm, D50=3.8μm, D90=7.2μm, Dmax=18.5μm, and the carbon content of the material is 10.5%.
[0119] Application Examples
[0120] 2025-type button cells were used to evaluate the electrochemical performance of the materials.
[0121] The button cell was prepared from the CR2025 battery shell for electrochemical performance testing and evaluation. The sodium ion positive electrode material used in the preparation of the pole piece was: CNT: VGCF: PVDF mass ratio 90: 0.8: 3.2: 6, using an appropriate amount of N-methyl-2-pyrrolidone as a solvent, and then ground with an agate mortar in a homemade glove box. The ground slurry was coated on aluminum foil using a 200-micron frame film maker, dried in a blast drying oven at 150 degrees for 1 hour, and then the punched pole piece was placed in a vacuum drying oven, and dried at 120 degrees, -0.1MPa vacuum for 12 hours. Later, a 15.6mm*0.6mm metal sodium sheet was used as the negative electrode to assemble a 2025 button cell, and the electrolyte was 1mol / LNaPF6+EC:PC:FEC (1:1:0.1 volume ratio).
[0122] The electrochemical test was conducted on a LANDHE blue electricity test system (CT3001A). The voltage window was set between 1.5-4.3V, 1C = 150mAh / g. After standing for 6 hours, 0.1C constant current charging was started, and constant voltage charging to 4.3V was performed. When the constant voltage charging current was less than 0.06C, the charging was terminated. Discharge began to 1.5V. The second cycle was performed.
[0123] Table 1 Electrochemical performance test results of Examples 1-8
[0124] Example 1 2 3 4 5 6 0.1CmAh / g 165.6 165.2 164.4 163.9 163.7 163.8 First Charge 165.6 165.2 164.4 163.9 163.7 163.8 Premiere 150.4 149.8 149.2 148.8 148.6 148.7 Initial efficiency % 90.82 90.68 90.75 90.79 90.78 90.78 Loop 100 times 94.07% 94.02% 94.05% 94.06% 94.04% 94.03% Loop 500 times 88.07% 88.03% 88.05% 88.06% 88.08% 88.04%
[0125] It should be understood that the above specific embodiments of the present invention are only used to illustrate or explain the principles of the present invention, and do not constitute a limitation of the present invention. Therefore, any modifications, equivalent substitutions, improvements, etc. made without departing from the spirit and scope of the present invention should be included in the protection scope of the present invention. In addition, the appended claims of the present invention are intended to cover all changes and modifications that fall within the scope and boundaries of the appended claims, or the equivalent forms of such scope and boundaries.
Claims
1. A method for preparing a polyanion-doped sulfate-carbon-coated sodium ion composite positive electrode material, characterized in that: The following steps are involved: (1) preparing a mixed solution of titanium citrate and ammonium sulfate; (2) mixing high-purity water, citric acid, vanadium salt, manganese salt, phosphate, sodium salt and the mixed solution obtained in step (1) to prepare a sodium ion positive electrode material precursor mixed solution; (3) heating the mixed solution obtained in step (2) to obtain a precursor sol; (4) then spray drying the precursor sol to obtain a precursor; (5) The precursor is sintered, crushed and dried under a protective gas atmosphere to obtain a polyanion-doped sulfate-carbon-coated manganese titanium vanadium sodium phosphate composite sodium ion positive electrode material.
2. The preparation method according to claim 1, characterized in that: The preparation process of the mixed solution of titanium citrate and ammonium sulfate is as follows: react high-purity TiO2 with concentrated sulfuric acid, then add high-purity water to obtain a high-purity titanyl sulfate solution; then add ammonia water to adjust the pH to 3-4 to obtain a mixture of white precipitate of metatitanic acid and ammonium sulfate; continue to add appropriate amount of citric acid and high-purity water to form a mixed solution of titanium citrate and ammonium sulfate.
3. The preparation method according to claim 2, characterized in that: In the preparation of a mixed solution of titanium citrate and ammonium sulfate, the molar ratio of TiO2 in high-purity TiO2 to sulfate and citric acid in concentrated sulfuric acid is 0.6:0.6:
1.
4. The preparation method according to claim 2, characterized in that: The reaction conditions of high-purity TiO2 and high-purity concentrated sulfuric acid are: 120℃ for 2h.
5. The preparation method according to claim 2, characterized in that: The manganese salt is manganese acetate tetrahydrate or manganese carbonate, the vanadium salt is ammonium metavanadate, the phosphate is sodium dihydrogen phosphate, and the sodium salt is sodium acetate or sodium carbonate; In terms of molar ratio, V in vanadium salt: Mn in manganese salt: sodium dihydrogen phosphate: Na in sodium salt: TiO2 = 0.4:1:2.6:0.8:0.6, the ratio of the total molar amount of high-purity water used to prepare the mixed solution of sodium ion positive electrode material precursor to the molar amount of manganese salt is (550-620):1, and the ratio of the total molar amount of citric acid used to prepare the mixed solution of sodium ion positive electrode material precursor to the mass of manganese salt is (2-3):
1.
6. The preparation method according to claim 2, characterized in that: The manganese salt is manganese acetate tetrahydrate or manganese carbonate, the vanadium salt is ammonium metavanadate, the phosphate is ammonium dihydrogen phosphate, and the sodium salt is sodium acetate or sodium carbonate; In terms of molar ratio, V in vanadium salt: Mn in manganese salt: diammonium hydrogen phosphate: Na in sodium salt: TiO2 = 0.4:1:2.6:3.4:0.6, the ratio of the total molar amount of high-purity water used to prepare the mixed solution of sodium ion positive electrode material precursor to the molar amount of manganese salt is (550-620):1, and the ratio of the total molar amount of citric acid used to prepare the mixed solution of sodium ion positive electrode material precursor to the mass of manganese salt is (2-3):
1.
7. The preparation method according to claim 1, characterized in that: In step (3), the mixed solution obtained in step (2) is heated to 80° C. and kept warm for 60-120 minutes.
8. The preparation method according to claim 1, characterized in that: In step (4), the temperature conditions for spray drying are: controlling the inlet air temperature at 300°C to 350°C and the outlet air temperature at 105-108°C.
9. The preparation method according to claim 1, characterized in that: In step (5), the sintering conditions are: in a protective gas atmosphere, heating to 700° C. within 240-360 minutes and keeping the temperature for 8-18 hours.
10. A polyanion-doped sulfate-carbon-coated sodium ion composite positive electrode material, characterized in that: The method is prepared by the method according to any one of claims 1 to 9.